2015
DOI: 10.1161/atvbaha.115.306474
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Splicing Variants Containing Extra Domain A Promote Atherosclerosis in Mice Through Toll-Like Receptor 4

Abstract: Objective Cellular fibronectin containing extra domain A (EDA+-FN) is abundant in the arteries of patients with atherosclerosis. Several in vitro studies suggest that EDA+-FN interacts with Toll-like receptor 4 (TLR4). We tested the hypothesis that EDA+-FN exacerbates atherosclerosis through TLR4 in a clinically-relevant model of atherosclerosis, the apolipoprotein E-deficient (Apoe−/−) mouse. Approach and Results The extent of atherosclerosis was evaluated in whole aortae and cross sections of the aortic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 31 publications
4
52
0
1
Order By: Relevance
“…The effects of FN isoforms on osteoclastogenesis may contribute to bone destruction due to the inflammatory microenvironment of radicular cysts (Khan et al , Khan et al , Liu et al ). Since the three main splice variants, EDA + FN, EDB + FN and CS1‐FN, are ligands of integrin receptors and Toll‐like receptor 4 (TLR4), interactions between FN isoforms and receptors in pre‐osteoclasts may directly affect osteoclastogenesis (Doddapattar et al , Jiang et al ), whilst their interaction in other cells could alter the expression of osteoclastogenic genes, such as vascular endothelial growth factor (VEGF) or IL‐17 (Liu et al , Lv et al ), by which osteoclastogenesis can be indirectly influenced. Therefore, this study explored the effects of FN isoforms on bone destruction in radicular cysts, as well as the underlying mechanism through antibody blocking and gene editing using the type II bacterial clustered, regularly interspaced, palindromic repeats (CRISPR)‐associated (Cas) system (Kohan et al , Wang et al 2015a, Wang et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of FN isoforms on osteoclastogenesis may contribute to bone destruction due to the inflammatory microenvironment of radicular cysts (Khan et al , Khan et al , Liu et al ). Since the three main splice variants, EDA + FN, EDB + FN and CS1‐FN, are ligands of integrin receptors and Toll‐like receptor 4 (TLR4), interactions between FN isoforms and receptors in pre‐osteoclasts may directly affect osteoclastogenesis (Doddapattar et al , Jiang et al ), whilst their interaction in other cells could alter the expression of osteoclastogenic genes, such as vascular endothelial growth factor (VEGF) or IL‐17 (Liu et al , Lv et al ), by which osteoclastogenesis can be indirectly influenced. Therefore, this study explored the effects of FN isoforms on bone destruction in radicular cysts, as well as the underlying mechanism through antibody blocking and gene editing using the type II bacterial clustered, regularly interspaced, palindromic repeats (CRISPR)‐associated (Cas) system (Kohan et al , Wang et al 2015a, Wang et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying TGFβ1 regulation by EDA+FN are currently largely unknown. Since EDA is a well-known endogenous ligand of TLR448, one hypothesis is that TLR4 pathway might be involved in the observed results. Our findings show increased NOX4 expression and activity in the aortas of mice lacking EDA expression, suggesting for this finding a mechanism independent of NOX4 activation by direct interaction with TLR-4 as described by Park et al 49 Moreover, in our study we found that the expression of TRAF-6, an important TLR-4 signalling pathway mediator, was not modified in the aorta of diabetic EDA −/− compared to wild type, suggesting that also classical TLR-4 signalling via TRAF6 is not directly involved in the increase of reactive oxygen species observed in that group.…”
Section: Discussionmentioning
confidence: 93%
“…Unlike for EDB + FN, several specific functions for EDA + FN in adult subjects have recently been described, mainly related to wound healing, tissue fibrosis, thrombosis and vascular wall integrity567. EDA + FN inclusion is highly restricted in adult healthy vessels but increases in vascular disease and in atherosclerosis8. In this setting, it contributes to plaque enlargement but also to its stabilization910.…”
mentioning
confidence: 99%
“…57 In agreement with those data, EDA is now shown to activate macrophages and promote atherosclerosis in a TLR4-dependent manner. 58 Interestingly, TLR4 deficiency was unable to reduce atherosclerosis in EDA-deficient mice, pointing to EDA as a prominent endogenous TLR4 ligand in the context of atherosclerosis. 58 Proliferation, apoptosis, and efferocytosis control plaque macrophage accumulation, and inflammation 59 and may alter the efficacy of anti-inflammatory therapy.…”
Section: Innate Immune Functionsmentioning
confidence: 99%
“…58 Interestingly, TLR4 deficiency was unable to reduce atherosclerosis in EDA-deficient mice, pointing to EDA as a prominent endogenous TLR4 ligand in the context of atherosclerosis. 58 Proliferation, apoptosis, and efferocytosis control plaque macrophage accumulation, and inflammation 59 and may alter the efficacy of anti-inflammatory therapy. 60 Data indicate that enhanced macrophage apoptosis limits the development of early atherosclerotic lesions, a stage with preserved efferocytosis.…”
Section: Innate Immune Functionsmentioning
confidence: 99%